À flor da pele/à flor da terra: o sintoma social MPB - Vicente, Maria de Fátima (2010)
This thesis deals with the social symptom Brazilian popular Music - MPB between 1965 and 1972 and its ethical incidence on the Brazilian society under dictatorship (1964-1985) as effect of its condition of social symptom. The sonority is a central element of the Brazilian society and instituted itself in earthly, corporal sonority, opposite to the sublime one. In the turn of century XIX, by the force of the conditions of the musical scene and the social-political scene, it was articulated based on the orality and for the percussion when, stabilished the frame song as the predominant way of the Brazilian musical culture. It points out as intrinsic factor to the definition of this frame the insurmountable presence of the singer, decisive element for the effect of symbolic mediation of the social link accomplished by this music, in special when the institutionalization of the MPB. The format song safeguarded the place of the body, as the frame supports itself the intonation of everyday speach, and instaurates the body of the singer as object of the circulation of the word, diction limited for the interdiction. Which alows to point out the acts of the singers as singular acts due to relation in this social symptom that the singer establishes with his public: situated in the lack of the object by the effect of musical silence, homologous position to the psychoanalyst in the cure, producing decoposed and understandable effects of the social reality. It was concluded that the vicissitudes of social MPB symptom in that social-political conjuncture, read by the paradigm of singer s interpretation , had happened in the society as acts that drive away the death and had accomplished understandable possibilities of the instituted social-political order